A Study on Beneficiaries of Mudra Yojna in Haryana - MANJEET; AGGARWAL, DR. NIPUN (The journal of contemporary issues in business and government, 2021)
Financial Inclusion is a process of providing the financial services and products to all, especially to weaker sections of the society in a cost-effective manner. Financial inclusion aims at ensuring a bank account for everyone and facilities such as payment, deposit, credits, transfer of funds, insurance, etc. Financial inclusion is considered to be crucial element for development of society. Mudra Yojna is a step by Indian government to attain financial inclusion. The paper attempts to analyse the usage of mudra Yojna by people in Haryana. No. of people who availed the facility of mudra Yojna in respect of Shishu loans, Kishore and Tarun loans during the year 2016-17 and 2017-18 along with amount sanctioned and disbursed were studied using secondary data. It has been found that the usage has increased in the year 2017-18 which indicates that people are not only aware of the scheme availability but are using it to meet the needs of their business whether start up or expansion